Failure of Good Faith in Mediating Divorce Cases in Religious Court - Muhammad Saifullah; Khoirul Anwar; Ali Murtadho; Ferry Khusnul Mubarok; Cecep Soleh Kurniawan (International Journal Ihya' 'Ulum al-Din, 2024)
Divorce mediation carried out outside the court (community) and within court, institutions has yet to be effective even though the government has issued a Supreme Court Regulation regarding mediation in court. The achievement of mediation success, which is still below 5%, has encouraged the Supreme Court to add an article on good faith (article 7, Supreme Court Regulation No. 1 of 2016) as a principle of mediation and the threat of sanctions for parties who do not have good faith. This study aims to reveal how the good faith clause is implemented in resolving divorce conflicts through mediation and sanctions for parties who do not act in good faith at the Pekalongan Religious Court. The data mining method was carried out through interviews with mediators, mediator judges at the Pekalongan Religious Court area, parties to the conflict, and experts in the field of mediation. Data mining was carried out through observational and documentation of domestic conflict studies. The collected data was analyzed through descriptive analysis. This paper concludes that (1) the principles of mediation have not been fully carried out in good faith in resolving divorce conflicts through mediation outside the court, so mediation fails and results in the neglect of protracted conflict issues, (2) mediation in the majority of courts lack of success due to internal and external factors, and (3) the mediator or mediator judge experiences difficulties in implementing sanctions against parties who do not have good intentions in resolving family conflicts. This research recommends that outsied of the court mediation be carried out by professional mediators who support the success of the mediation process in the justice system.